2014
DOI: 10.1177/2049463714547115
|View full text |Cite
|
Sign up to set email alerts
|

Splice variation of the mu-opioid receptor and its effect on the action of opioids

Abstract: Summary points1. An individual's response to opioids is influenced by a complex combination of genetic, molecular and phenotypic factors. 2. Intra-and inter-individual variations in response to mu opioids have led to the suggestion that muopioid receptor subtypes exist. 3. Scientists have now proven that mu-opioid receptor subtypes exist and that they occur through a mechanism promoting protein diversity, called alternative splicing. 4. The ability of mu opioids to differentially activate splice variants may e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…MORs are encoded by a single structural gene (Opioid receptor mu 1, Oprm1 ) consisting of 4 exons. Exon 1 codes for the extracellular N‐terminal and first transmembrane domain, exons 2 and 3 for the remaining transmembrane domains and exon 4 for amino acids of the C‐terminal region . We analyzed Oprm1 mRNA levels by using RT‐SYBR green quantitative PCR assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MORs are encoded by a single structural gene (Opioid receptor mu 1, Oprm1 ) consisting of 4 exons. Exon 1 codes for the extracellular N‐terminal and first transmembrane domain, exons 2 and 3 for the remaining transmembrane domains and exon 4 for amino acids of the C‐terminal region . We analyzed Oprm1 mRNA levels by using RT‐SYBR green quantitative PCR assay.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show that the elevated MOR mRNA expression corresponds to the increase in protein levels and for the enhancement of the functional response to MOR activation. The Oprm1 gene undergoes extensive splice variants, and several of these are functionally relevant . We focused on the MOR‐1S and MOR‐1T splice variants, which are the most abundantly expressed in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing appreciation that individuals may responded differently to opioids due to variants of the opioid receptor. The opioid receptor mu has several polymorphisms and variants, which may be associated with differences in morphine‐induced cell signals …”
Section: Discussionmentioning
confidence: 99%
“…The opioid receptor mu has several polymorphisms and variants, which may be associated with differences in morphine-induced cell signals. [89][90][91] Dever et al 92 showed that MOR variants may be differently regulated in patients with HIV who have varying levels of neurocognitive impairment. Hypothetically, therefore, when exploring the effects of opioids on cognition, the influence of genetic and molecular factors should also be considered as contributing to individual responses.…”
Section: Pain Opioids and Cognitionmentioning
confidence: 99%
“…It is hypothesized that compounds promoting G signaling will produce analgesia while avoiding the β-arrestin complex-dependent effects leads to less respiratory depression [106]. The presence of several OPRM1 splice variants leads to a different efficacy of each opioid receptor [107], where each splice variant may exhibit a distinct pharmacological profile explaining the different opioid consumptions between individuals [108]. μopioid receptor heterodimerization further diversifies the possible opioid response since dimerization will affect intracellular pathways [109,110].…”
Section: Pharmacodynamic Factors Affected By Polymorphisms μ-Opioid Rmentioning
confidence: 99%